Philosophy of education in action : an inquiry-based approach - Nicholson, D. W. (New York Routledge, 2022)
"Philosophy of Education in Action: An Inquiry-Based Approach (Second Edition) is an innovative introductory text that invites readers to explore philosophy of education through the lens of their own observations and experiences. Using the "Wonder Model of Inquiry," readers investigate the purposes of education, how schools are designed to fulfill those purposes, and the influence of philosophy on educational practices. Grounded in authentic classroom vignettes and supported by examples from actual schools and educational programs, readers think critically and creatively about philosophical issues. Probing questions analyze the curriculum, examine pedagogy, conceptualize the role of the teacher and student in the learning process, and explore the role of school organization and design. Readers are guided to reflect upon their own practices and articulate their own philosophical beliefs. Readers also imagine and design a hypothetical school using project-based methods to interpret, synthesize, and evaluate different educational philosophies. The "Continuum of Educational Philosophy" locates practices in relation to philosophical perspectives. The second edition includes updated sources and examples of schools and programs that represent different philosophical perspectives. In addition to applying the "3Cs" criteria of evaluation, two new chapters highlight voices that respond to and challenge different educational philosophies. The final chapter adds guidance on how to construct and compose a personal philosophy of education statement"--
Includes bibliographical references and index.
Keywords: Education -- Philosophy; Inquiry-based learning